Bilateral lacrimal gland tumor as a manifestation of renal posttransplant lymphoproliferative disorder. Case report - Aranda Villalobos, Dora (2018)
Posttransplant lymphoproliferative disorder (PTLD) is an uncommon complications of solid organs and allogeneic bone marrow transplants associated with the use of immunosuppressive agents. The presentation in the lacrimal gland is rare. We report the case of a 27 year old female patient undergoing renal transplantation receiving immunosuppressive treatment (tacrolimus, mycophenolate mofetil and everolimus); she presents a supero-external angle tumor of the left orbit, in relation to the lacrimal gland according to the orbit tomography. Surgical resection of the tumor was performed, the pathology report was: plasmocytic hyperplasia. Later it presents tumor in both orbits, it is indicated rituximab, with total remission of the tumor that is confirmed with tomography study of orbits.